The mechanism of antiproliferative activity of the oxaliplatin pyrophosphate derivative involves its binding to nuclear DNA in cancer cells - Prachařová, Jitka; Kostrhunová, Hana; Barbanente, Alessandra; Margiotta, Nicola; Brabec, Viktor (JBIC, Journal of biological inorganic chemistry, 2023)
(1R,2R-diaminocyclohexane)(dihydropyrophosphato) platinum(II), also abbreviated as RRD2, belongs to a class of potent antitumor platinum cytostatics called phosphaplatins. Curiously, several published studies have suggested significant mechanistic differences between phosphaplatins and conventional platinum antitumor drugs. Controversial findings have been published regarding the role of RRD2 binding to DNA in the mechanism of its antiproliferative activity in cancer cells. This prompted us to perform detailed studies to confirm or rule out the role of RRD2 binding to DNA in its antiproliferative effect in cancer cells. Here, we show that RRD2 exhibits excellent antiproliferative activity in various cancer cell lines, with IC50 values in the low micromolar or submicromolar range. Moreover, the results of this study demonstrate that DNA lesions caused by RRD2 contribute to killing cancer cells treated with this phosphaplatin derivative. Additionally, our data indicate that RRD2 accumulates in cancer cells but to a lesser extent than cisplatin. On the other hand, the efficiency of cisplatin and RRD2, after they accumulate in cancer cells, in binding to nuclear DNA is similar. Our results also show that RRD2 in the medium, in which the cells were cultured before RRD2 accumulated inside the cells, remained intact. This result is consistent with the view that RRD2 is activated by releasing free pyrophosphate only in the environment of cancer cells, thereby allowing RRD2 to bind to nuclear DNA.
Keywords: Neoplasms; nádory; oxaliplatin; organoplatinové sloučeniny; difosfáty; platina; Platinum; Diphosphates; DNA; Organoplatinum Compounds; cisplatina; Antineoplastic Agents; protinádorové látky; Cisplatin; Oxaliplatin